An approach to assess the consequence of a hypothetical radionuclide release in Singapore - a densely populated urban setting - Chai , Siao Yang; Sun, Xiangming (Nuclear Science and Technology, 2026)
This study is to demonstrate an approach to investigate the consequence of a hypothetical radionuclide release scenario in Singapore, a typical urban setting with high population density. To this end, we made use of MACCS 4.1, a Gaussian-based atmospheric dispersion model to compute the peak dose and the population health effects. We developed the meteorological and site files from data provided by local government agencies. Our investigation showed that the chosen scenario poses very little to negligible risk to the health of local population as the peak dose received across the country is below the radiation safety level recommended by ICRP